How the GEMOY Game Supports Literacy Development: Insight from Secondary EFL Students Responses - Primasari, Yusniarsi; Supriyono; Lestari, Yayuk Dwi; Sari, Hesty Puspita (Faculty of Tarbiyah, Institut Agama Islam Negeri (IAIN) Kediri, Indonesia, 2024)
Literacy is crucial for learning because it helps students understand and work with written materials, but many students today have difficulties with reading, which affects their overall school performance. This study explores the effectiveness of the GEMOY (Gleaming English Game for Youth) in enhancing literacy skills among secondary EFL students of SMPN 2 Dongko Trenggalek. Utilizing a quantitative approach, responses were collected from 25 students who engaged with the GEMOY game as part of their learning process. Data were collected through closed-ended interviews with a Likert scale to assess students' responses to the game's effectiveness in improving their literacy. Data were analyzed using descriptive statistics to determine the overall trend in students' perceptions of the GEMOY game. Secondary EFL students reported an average score of 4.20 for understanding English texts, 4.40 for effectiveness in expanding vocabulary, 4.10 for effectiveness in helping students identify main ideas, and 4.00 for improving sentence writing. These results indicate that GEMOY effectively enhances literacy development by providing an engaging and interactive learning experience. The study highlights the potential of educational games to address gaps in traditional literacy instruction methods and offers valuable insights into integrating game-based learning. The findings suggest that incorporating GEMOY into English language teaching can significantly benefit EFL students by making literacy instruction more dynamic and effective.